STUDI KARAKTERISTIK CAMPURAN PERKERASAN LAPIS TIPIS ASPAL BETON (HRS-WC) DENGAN MENGGUNAKAN MATERIAL DARI SUNGAI BAHOMANTE DAN MATERIAL SUNGAI LASAMPI - Rahman, Rahmatang; Mashuri, Mashuri (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
Asphalt concrete pavement mix should use material that meets specifications. Road construction in Morowali Regency uses material from Stone Crushero of Bahomante River and Lasampi River from Morowali. The purpose of this research is to understand the characteristic of HRS pavement mixture using Stone Crusher material of Bahomante River and River Lasampi. Determination of aggregate composition on HRS mixture was using sieve method. The gradation used in this study is the ideal gradation. The determination of optimum asphalt content (PKAO) was made using 6 variations of asphalt contents that are 6.0%, 6.5%, 7.0%, 7.5%, 8.0% and 8.5%. CharacteristicÂ  testing using Marshall tools. The results of this study shows that the HRS mixture using the Stone Crusher material of the Bahomante River has hight density and stability compared to the mixture of HRS which uses a mixture of Stone Crusher material of Bahomante River and Lasampi River. The study also found that the KAO blend of HRS using Stone Crusher material Bahomante tends to be similar to that of a mixed HRS KAO that uses a combination of Stone Crusher material of Bahomante River and Lasampi River.